2016
DOI: 10.17718/tojde.09900
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Classroom Community and Team Development Process in Online Learning

Abstract: The purpose of this study is to determine whether there is a relationship between Turkish online learners' sense of classroom community, perceptions of success in team development process and their preferences of studying in teams. A survey instrument included the Sense of Classroom Community Scale, Tuckman's Teamwork Questionnaire and some other items were used to collect data. The study has shown that there is a medium level relationship between online learners' sense of community and their perceptions of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…Widely known as an effective team building design for the educational setting (Riebe et al, 2010;Aydin & Gumus, 2016;Weber & Karman, 2017), Tuckman approach (1965 remains famous for team development model and it is still known for its four-sequential stages (Kur, 1996;Largent, 2016;Manges et al, 2017). Forming is the first interaction of team members, when they become familiar with each other, concentrating efforts to find out which behaviors are acceptable regarding their tasks, feeling confused on how to act and unsure about the benefits of team participation.…”
Section: Team Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Widely known as an effective team building design for the educational setting (Riebe et al, 2010;Aydin & Gumus, 2016;Weber & Karman, 2017), Tuckman approach (1965 remains famous for team development model and it is still known for its four-sequential stages (Kur, 1996;Largent, 2016;Manges et al, 2017). Forming is the first interaction of team members, when they become familiar with each other, concentrating efforts to find out which behaviors are acceptable regarding their tasks, feeling confused on how to act and unsure about the benefits of team participation.…”
Section: Team Buildingmentioning
confidence: 99%
“…Tuckman & Jensen (1977) formally extended the original model and added a fifth stage, adjourning, to provide opportunity for acknowledgements. Since then, the model was studied, applied and successfully validated in many team development fields, remaining strongly accepted (Largent, 2016;Aydin & Gumus, 2016;Manges et al, 2017). An Indonesian research has recently used Tuckman model as a theoretical reference to investigate virtual team performance of Binus University e-learning student's capability of solving teamwork problems (Siregar et al, 2018).…”
Section: Team Buildingmentioning
confidence: 99%
“…Termasuk dalam klasifikasi academic fraud adalah penugasan kepada mahasiswa yang harus dikerjakan secara kelompok tetapi hanya dikerjakan oleh beberapa mahasiswa atau bahkan hanya dikerjakan oleh ketua kelompok. "The online learners in Turkey generally prefer individual study rather than the teamwork" (Erdem Aydin & Gumus, 2016).…”
Section: Pendahuluanunclassified
“…In the data analysis, it was found that exposure to e-profiles of distant team members reduced task conflict among them. In similar research done on Turkish online students, the sense of classroom community positively impacted the team learning behavior (Erdem & Gumus, 2016). Similarly, many other study have shown a positive relationship between sense of community and team learning behaviors such as information sharing and the creation of shared commitment to achieving collective goals (Bruffe, 1993;Ded, 1996;Wellman, 1999).…”
Section: Sense Of Community and Team Learning Behaviormentioning
confidence: 71%